The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1974
DOI: 10.1161/01.cir.50.2.331
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Size and Function and Heart Size in the Year Following Myocardial Infarction

Abstract: SUMMARYInterrelationships among left ventricular (LV) size, LV function, and heart size were investigated in 49 patients studied 2-12 months after myocardial infarction. LV end-diastolic volume (EDV) and ejection fraction (EF) were determined by biplane ventriculography. Heart size was estimated from chest films by the cardiothoracic ratio (CTR) and cardiac volume (CV) methods. Ventricular function (i.e., EF) was related to chamber size (i.e., EDV), but the correlation coefficient was not high (r = 0.74); thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…LVEDV/LVESV negatively correlated with LVEF. In general, the bigger cardiac size is, the worse cardiac function becomes (23). Therefore, increases in PhHB/PhSD indicate LV structural and functional changes.…”
Section: Relationship Between Lvedv/lvesv and Phhb/phsdmentioning
confidence: 99%
“…LVEDV/LVESV negatively correlated with LVEF. In general, the bigger cardiac size is, the worse cardiac function becomes (23). Therefore, increases in PhHB/PhSD indicate LV structural and functional changes.…”
Section: Relationship Between Lvedv/lvesv and Phhb/phsdmentioning
confidence: 99%
“…Left ventricular dilatation usually signifies prior myocardial infarction, or association of another form of acquired cardiovascular disease, such as chronic systemic hypertension. Left ventricular function in these patients is usually impaired [14]. The radiographic appearance of the heart in patients having their first acute myocardial infarction has important prognostic value.…”
Section: Acute Myocardial Infarctionmentioning
confidence: 99%
“…The radiographic appearance of the heart in patients having their first acute myocardial infarction has important prognostic value. Normal cardiac size after acute myocardial infarction is associated with better cardiac function [14] and outcome [15].…”
Section: Acute Myocardial Infarctionmentioning
confidence: 99%
“…Previous studies have shown that an ACS < 8% has no demonstrable effect on LV function. [1][2][3] Thus, the inability of 20'Tl scintigraphy to detect scars of this size is not a great disadvantage. A negative 20'Tl myocardial scintigram does not exclude the possibility of a prior infarction, but makes the presence of a significant scar highly unlikely.…”
Section: Quantitative Correlation Of 21'ti Scintigraphic Scar Sizementioning
confidence: 99%